Precision enhanced alignment bonding technique with sacrificial strategy - Li, Qian; Ye, Zi; Liu, Mingyang; Liu, Wei; Zhang, Pan; Sun, Xiao; Zhang, Huimin; Li, Zhenming; Gui, Lin (Frontiers in Bioengineering and Biotechnology, 2023)
Quick but accurate (< 5 μm) face-to-face bonding is critical and difficult in multilevel microfluidic chip fabrication. This work proposes an “N2-1” sacrificial strategy to help to improve the accuracy of the bonding technique from the existing level: The target micropattern is copied N2 times, and (N2-1) of them are sacrificed to obtain the most accurate alignment. Meanwhile, a method for manufacturing auxiliary liquid metal alignment lines on transparent materials is proposed to visualize auxiliary marks and facilitate the alignment. Though the principle and procedure of alignment are straightforward, the alignment accuracy substantially improved compared to the original method. According to the numerical simulation, the fabrication of a liquid metal based electroosmotic micropump with vertically placed electrodes requires bonding of the upper and lower electrodes to an accuracy of 3.415 μm. With this technology, we have successfully fabricated a high-precision 3D liquid metal based electroosmotic micropump just using a conventional desktop aligner. Because of the high precision during the alignment, the flow velocity is up to 435.62 μm/s at a driven voltage of 40 V, which far exceeds the previous similar reports.